Influence Promotions, Electronic Word of Mout , and Prices Regarding Purchasing Decisions - Nur Hamidah, Shofiatul; Qristin Violinda; Noni Setyorini (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Study This study influence Promotion , Electronic Word of Mouth, and Price on Consumer Purchasing Decisions drinking water products in Ades packaging in Semarang City. Study This done with method study quantitative, population study This that is consumers who have do purchase drinking water products in Ades packaging in Semarang City. Study This use with purposive sampling technique, and collected data from 96 respondents. Data collection methods in research This use questionnaire with technique SEM (Structural Equation Modeling) analysis on software SmartPLS 3.29 as tool help in analysis study . Research result show that promotion influential on purchasing decisions, electronic word of mouth does not influential on purchasing decisions , price No influential on purchasing decisions.